The Effect of Financial Performance and Sustainability Performance on Stock Prices with Earnings Management as a Moderating Variable in the Coal Sub-Sector of Southeast Asia 2022-2024 - Armiyani, Nora Arum; Kusuma, Marhaendra; Kusumaningarti, Miladiah (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to analyze the effect of financial performance and sustainability performance on stock prices, as well as to examine the moderating role of earnings management in coal sub-sector companies in Southeast Asia. The study uses secondary data obtained from financial statements and sustainability reports of coal companies in Southeast Asia during the 2018–2022 period with a total of 105 observations. The data were analyzed using multiple linear regression and Moderated Regression Analysis (MRA) with the assistance of SPSS version 26.The results indicate that financial performance has a positive and significant effect on stock prices, while sustainability performance does not have a significant effect. Furthermore, earnings management is proven to moderate the relationship between financial performance and stock prices positively, but it negatively moderates the relationship between sustainability performance and stock prices. This study contributes to the finance and sustainability literature by integrating financial performance, sustainability performance, and earnings management practices into a single research model within the coal sector in Southeast Asia. Previous studies mostly focused on the direct relationship between financial or ESG performance and stock prices, while this study highlights the role of earnings management as both a strengthening and weakening factor in such relationships. This research provides practical implications for investors to consider not only profitability but also governance transparency in order to avoid information distortion caused by earnings management. For regulators, the findings can serve as a basis for strengthening sustainability reporting requirements in coal companies. For corporate management, the study emphasizes the importance of integrating sustainability with sound governance practices to enhance long-term firm value.